Angiotensin receptor blockers use and lung cancer risk in Chinese patients with chronic obstructive pulmonary disease: a population-based cohort study - Wenhao Li; Qingqing Yang; Yahong Chen; Yexiang Sun; Peng Shen; Feng Sun; Jinzhu Jia (Respiratory Research)
Abstract Background Chronic obstructive pulmonary disease (COPD) is one of the most prevalent specific chronic respiratory diseases. It could worsen the development of cardiovascular diseases (CVD) and lung cancer. We aimed to elucidate the relationship between the use of angiotensin receptor blockers (ARBs) and the incidence of lung cancer among the COPD population in China. Methods This retrospective cohort included COPD patients identified by the international classification of diseases 10th edition (ICD-10) codes in the Yinzhou Regional Health Care Database. The use of ARBs was defined according to the use and cumulative use. The lung cancer was defined by ICD-10 code (up to 2023). Time-varying Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of the use of ARBs on the risk of lung cancer. Results This population-based COPD cohort comprised 25,436 patients with an average age of 68.2 years (standard deviation [SD]: 12.59 years), of which 60.6% were male. A total of 8,611 patients received at least one prescription for ARBs. After adjusting for multiple covariates, the results showed that cumulative annual exposure to ARBs was associated with a reduced risk of lung cancer (HR: 0.93, 95% CI: 0.90–0.97). The results of sensitivity analyses and negative control exposure analyses indicated that the associations were largely consistent and less likely to be influenced by unobserved confounding. Conclusions The use of ARBs may reduce the risk of lung cancer among patients with COPD.